Use of an automatic device for the determination of mechanical properties on photoelastic samples of small dimensions - Prado,Felipe Maia (2020)
Abstract Photoelastic materials and Photoelasticity have been very effective in the study of the effects of stress and strain in materials such as iron, steel, concrete, etc. However, mainly because of human interaction, systematic errors are introduced during the measurement process, which directly affects the final result. When using small photoelastic samples, these types of errors can escalate due to the increased difficulty of handling. Intending to minimize systematic errors in the process of data collection, this work presents the use of an automatic loading device, developed by us, to apply mechanical stresses in small photoelastic samples. The device created has shown great effectiveness in photoelastic applications that uses a transmission polariscope, but it can also be used in other photoelastic techniques, such as reflection photoelasticity, as well as in other areas of optics such as Holography and Speckle. An important benefit is the ease and speed of handling that can improve the organization and quality of the activities in labs of optics.